Regulation of Digital Assets and Financial Technologies in the UK: Current Status and Future Prospects ("Journal "U". Economy. Management. Finance.", 2023)
This article considers the legislative regulation of digital assets and financial technologies in the UK. The authors note that the UK is one of the most progressive countries regarding the regulation of the digital assets and financial technologies. There is an active debate about the full legislative regulation of this area, and the common law courts have long had their own views on certain issues. Taking into account the development of digital technologies and the expanding use of digital assets, the study of foreign experience contributes to the formation of a legal position for the future regulation of this issue in the Russian Federation.
Keywords: digital assets; financial technology; financial services; cryptocurrency; regulation; financial market; United Kindom